Perception of plastic surgery in the society - Agarwal, Pawan (Indian Journal of Plastic Surgery, 2004)
The perception of plastic surgery in society is limited and underestimates the versatility of the specialty. A survey was conducted in order to assess knowledge and to provide some initial evidence for education about the scope of plastic surgery amongst the public, medical and nursing students and general practitioners. A questionnaire was devised and four population groups of respondents were surveyed at random in one district. The results reveal that the majority of the public needs more information about the benefits that our specialty can offer them. Plastic surgeons are mainly associated with burns and cosmetic surgery and they are not necessarily identified as primary surgeons for procedures fundamental to our specialty. If patients are to receive the best treatment available, it is essential that we educate the public about our clinical interests and activities.
Keywords: Perception; plastic surgery; image; society